Isolation and screening of rhizobacteria from soil in Ngawi, East Java,as candidates of agent for liquid organic fertilizer production - HARTATI IMAMUDDIN; TIRTA KUMALA DEWI; SARJIYA ANTONIUS (Nusantara Bioscience, 2015)
Abstract. Imamuddin H, Dewi TK, Antonius S. 2015. Isolation and screening of rhizobacteria from soil in Ngawi, East Java as candidates of agent for liquid organic fertilizer production. Nusantara Bioscience 7: 107-111. A series of activities have been done to find indigenous microbes from Ngawi, East Java, as candidates for living organic fertilizers. The study was started with sampling of soils from 17 locations in Ngawi. Then, the samples were isolated to get population of soil microbes, including total, phosphate-solubilizing, N-fixing, and IAA-(Indol Acetic Acid)-producing bacteria. Five soil samples were used to test bacterial growth in several concentration of propoxur. Method of isolation used in this study was enrichment culture and the growth was determined using spectrophotometer at 436 nm wave length. The resuts showed that the populations of total and IAA-producing bacteria in Ngawi soil were relatively high, namely 106 CFU/g soil, but the population N-fixing bacteria was only 10-5, and no phosphate-solubilizing bacteria could grow. Twenty one isolates of bacteria were found, 16 of which postively produced IAA and 5 isolates of which could grow in  propoxur medium. The highest production of IAA was found in sample number 6.3 with a concentration of 123.535 ppm and isolate H-2-NG (sample number 2) could grow at concentration of 1000 ppm (MM medium)-3000 ppm (MSB medium). It is hoped that these isolates can be used as candidates of agent for liquid living organic fertilizers.